(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Any speech should be informative in the first place. The main feature of the information is that it should be accurate. The first information is taken from public life, if it is not based on concrete facts, it will lead to the discrediting of the speaker. Every piece of information requires a serious and scientific approach. Today, information is rapidly reaching television, radio, the Internet, and newspapers and magazines. The challenge in modern public speaking is to be able to distinguish information correctly.